Utilizing M-Reader for Extensive Reading: Implications for Seminarian Identity at Mataloko Seminary - Yohanes Capistrano Satrini Lobi; Thomas Wahyu Prabowo Mukti (Universitas Hamzanwadi, 2023)
Introduced in 2021, M-Reader is a digital application designed to promote Extensive Reading. Mataloko Seminary, recognizing its potential, has employed M-Reader to enhance both student literacy and identity formation. With this context in mind, this research sought to answer two pivotal questions: (1) How has Mataloko Seminary integrated Extensive Reading into its curriculum? and (2) To what extent does Extensive Reading via M-Reader influence the identity of seminarians on their journey to priesthood? Employing a narrative inquiry methodology, the study meticulously examined the application of M-Reader in extensive reading practices and its consequent impact on seminarian identity. Data was meticulously collated through semi-structured interviews with three students from grades 10 and 12, all hailing from Mataloko. This data, systematically categorized and analyzed using Microsoft Excel, revealed that M-Reader-supported extensive reading at Mataloko Seminary adheres to ten established principles of extensive reading. Furthermore, the program emerged as a pivotal tool in molding the seminarians' identity across four critical dimensions: human, intellectual, pastoral, and spiritual. These findings underscore the potential benefits for other educational institutions targeting comprehensive identity development: the incorporation of digital extensive reading tools like M-Reader can be a game-changer.